2016
DOI: 10.1074/jbc.m116.751453
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized Guanine Base Lesions Function in 8-Oxoguanine DNA Glycosylase-1-mediated Epigenetic Regulation of Nuclear Factor κB-driven Gene Expression

Abstract: A large percentage of redox-responsive gene promoters contain evolutionarily conserved guanine-rich clusters; guanines are the bases most susceptible to oxidative modification(s). Consequently, 7,8-dihydro-8-oxoguanine (8-oxoG) is one of the most abundant base lesions in promoters and is primarily repaired via the 8-oxoguanine DNA glycosylase-1 (OOG1)-initiated base excision repair pathway. In view of a prompt cellular response to oxidative challenge, we hypothesized that the 8-oxoG lesion and the cognate repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
253
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(272 citation statements)
references
References 70 publications
(94 reference statements)
17
253
1
1
Order By: Relevance
“…Hif1α, STAT1, NF-κB and MYC) in conjunction with OGG1 protein and, in turn, regulates the expression of important genes involved in cancer development, such as VEGF [40], SIRT-1 [41] and inflammatory genes such as TNF-α and CXCL2 [42]. Interestingly, this last role of OGG1 on inflammatory genes may explain the reduced inflammatory response in Ogg1 −/− mice [43].…”
Section: Unusual Involvement Of Ber Enzymes In the Regulation Of Genementioning
confidence: 99%
“…Hif1α, STAT1, NF-κB and MYC) in conjunction with OGG1 protein and, in turn, regulates the expression of important genes involved in cancer development, such as VEGF [40], SIRT-1 [41] and inflammatory genes such as TNF-α and CXCL2 [42]. Interestingly, this last role of OGG1 on inflammatory genes may explain the reduced inflammatory response in Ogg1 −/− mice [43].…”
Section: Unusual Involvement Of Ber Enzymes In the Regulation Of Genementioning
confidence: 99%
“…Given the abundance of PQS in the promoter regions throughout the genome (12,13), the generality of the proposed mechanism may be very likely. Supporting this view is the fact that Fleming et al also provide a more comprehensive mechanistic explanation for the DNA oxidation and BER-dependent transcriptional activation reported in several cellular studies (4,10,11,21). In each case, the target gene investigated turned out to contain a PQS in its promoter (8).…”
mentioning
confidence: 51%
“…Most oxidative DNA damage is efficiently processed by DNA repair pathways, primarily base excision repair (BER), the molecular details of which are generally well understood (2). However, an emerging area of research posits that certain oxidative DNA lesions and their associated repair complexes are intermediates in a signaling transduction cascade that uses ROS as secondary messengers to ultimately effect transcriptional regulation (3)(4)(5)(6)(7). In PNAS, Fleming et al (8) reinforce these notions by describing a compelling mechanism by which 8-oxoguanine (OG), a canonical oxidative DNA damage product, when occurring in guanine-rich, G-quadruplex-forming promoter sequences, directly up-regulates transcription of the downstream gene.…”
mentioning
confidence: 99%
“…This provides a precedent that controlled DNA damage and repair can regulate active transcription. Other studies have also shown that site specific DNA damage can activate gene transcription (Ba et al 2014;Fleming, Ding, and Burrows 2017;Pan et al 2016;Pastukh et al 2015), though the mechanism through which damage occurs to specific points in the genome remains relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, oxidative damage to the vascular endothelial growth factor (VEGF) promoter enhances binding of hypoxiainducible factor 1a (HIF1a) with the subsequent assembly of BER components activating gene expression Ruchko 2009, 2010;Pastukh et al 2015). A similar process occurs in the promoters of tumor necrosis factor a (TNF-a) (Pan et al 2016) and sirtuin 1 (SIRT1) (Antoniali et al 2014). Controlled induction of gene transcription then requires activation of BER through OGG1…”
Section: Journal Of Biological Chemistry 5457mentioning
confidence: 99%